Satisfaction's consequences - East, Robert (Henry Stewart Talks, 2008)
Retention/defection, positive and negative word of mouth to other consumers, and compliment and complaint to suppliers, There is a weak correlation between satisfaction and retention, Stronger correlation between dissatisfaction and defection, Satisfaction usually predicts word of mouth quite strongly, New research confirms these patterns and explanations are given, Satisfaction is linked to later company performance and share price rise but it is not clear yet how these changes come about, Dissatisfaction lies behind complaining but other factors are involved, Managerial implications of this work